Material didáctico sensorial para el desarrollo del ámbito lógico matemáticas en niños y niñas de 4 a 5 años del subnivel inicial II, de la unidad educativa “Ángel Polibio Chaves” del cantón Guaranda, provincia bolívar, en el periodo 2024. - Aldaz Agualongo, Henry Damian (2024)
The purpose of this research project is the investigation and evaluation of the sensorial didactic material as elements that favor the development of the logical- mathematical area in children from 4 to 5 years old, which are integrated in the initial level II of the Educational Unit “Àngel Polibio Chaves” of the Guaranda Canton, Bolivar province, in the period 2024. With this study, carried out through a qualitative approach, an exhaustive analysis was proposed regarding the implementation of this type of material that can have a positive impact on the development of the logical-mathematical field, learning of basic concepts and progress of sensory skills in children that are significant at this stage of education. It should be emphasized that sensorial didactic materials can be a crucial part of the integral development of children, since they facilitate the learning process in a participatory, meaningful and fun way. This study provides a valuable contribution to the field of early education and child development, highlighting the importance of the use of materials from different textures with which several basic concepts can interact, as well as the benefit it provides in fine motor skills by making precise movements, gross motor skills with large movements, highlighting the use of sensory systems from the senses themselves, achieving the development of mathematical, motor, cognitive and sensory logical skills, throughout the educational process of children in early childhood level II